Symbolism of the Siraman Ceremony as a Formative Framework for Faith, Identity and Communal Belonging in ALMA Puteri’s Perpetual Vows - Teresia Derung; Lorentius Goa; Rosalia Ina Kii; Leo Danan; Didimus Kebesa Werang; João Francisco Maia (Center for Research and Development of Religious Literature and Heritage, 2025)
The siraman (shower) ceremony performed before the perpetual vows of ALMA Puteri in Indonesia represents a unique case of ritual inculturation in Catholic religious life. Nevertheless, its symbolic reinterpretation within a consecrated-vows context has not been systematically examined. This study aims to address this gap by analyzing how the siraman ritual functions as a symbolic, theological and social mediator in the vocational formation of ALMA Puteri candidates. Using a qualitative descriptive–analytical design, data were collected through participant observation, semi‑structured interviews with ten sisters who underwent the ritual, and document analysis. The data were coded thematically and analyzed using Miles and Huberman’s interactive model. he findings reveal three key insights. First, the ritual’s symbolic elements such as blessed water, purple garments, jasmine decorations, and the use of traditional vessels, embody themes of purification, repentance and vocational readiness. Second, the ceremony strengthens communal identity by involving leaders, formators and family members, thereby reinforcing social support and ecclesial belonging. Third, the ritual recontextualizes Javanese cultural symbols within Catholic theological anthropology, demonstrating how indigenous practices can enrich spiritual formation. These findings highlight the siraman ceremony as a meaningful locus of inculturation that integrates cultural heritage with Catholic consecrated life. The study concludes that such rituals can deepen spiritual identity and recommends further research on intercultural formation in women’s religious communities.